ADAMTS-15 Has a Tumor Suppressor Role in Prostate Cancer - Marley J. Binder; Scott McCoombe; Elizabeth D. Williams; Daniel R. McCulloch; Alister C. Ward (Biomolecules, 2020)
Extracellular matrix remodeling has emerged as an important factor in many cancers. Proteoglycans, including versican (VCAN), are regulated via cleavage by the proteolytic actions of A Disintegrin-like And Metalloproteinase domain with Thrombospondin-1 motif (ADAMTS) family members. Alterations in the balance between Proteoglycans and ADAMTS enzymes have been proposed to contribute to cancer progression. Here, we analyzed the expression of ADAMTS-15 in human prostate cancer, and investigated the effects of enforced expression in prostate cancer cell lines. ADAMTS-15 was found to be expressed in human prostate cancer biopsies with evidence of co-localization with VCAN and its bioactive cleavage fragment versikine. Enforced expression of ADAMTS-15, but not a catalytically-inactive version, decreased cell proliferation and migration of the ‘castrate-resistant’ PC3 prostate cancer cell line in vitro, with survival increased. Analysis of ‘androgen-responsive’ LNCaP prostate cancer cells in vivo in NOD/SCID mice revealed that ADAMTS-15 expression caused slower growing tumors, which resulted in increased survival. This was not observed in castrated mice or with cells expressing catalytically-inactive ADAMTS-15. Collectively, this research identifies the enzymatic function of ADAMTS-15 as having a tumor suppressor role in prostate cancer, possibly in concert with androgens, and that VCAN represents a likely key substrate, highlighting potential new options for the clinic.